2016
DOI: 10.1111/eva.12338
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing shows sleeping sickness relapse is due to parasite regrowth and not reinfection

Abstract: The trypanosome Trypanosoma brucei gambiense (Tbg) is a cause of human African trypanosomiasis (HAT) endemic to many parts of sub‐Saharan Africa. The disease is almost invariably fatal if untreated and there is no vaccine, which makes monitoring and managing drug resistance highly relevant. A recent study of HAT cases from the Democratic Republic of the Congo reported a high incidence of relapses in patients treated with melarsoprol. Of the 19 Tbg strains isolated from patients enrolled in this study, four pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…HIV takes advantage of the fat as a viral reservoir during the chronic stage of infection, and persistence on this reservoir is an obstacle for treatment ( Chun et al., 2015 ). It is possible that persistence of T. brucei in the fat may also account for some of the treatment failures in humans ( Richardson et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…HIV takes advantage of the fat as a viral reservoir during the chronic stage of infection, and persistence on this reservoir is an obstacle for treatment ( Chun et al., 2015 ). It is possible that persistence of T. brucei in the fat may also account for some of the treatment failures in humans ( Richardson et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trindade et al have shown, using transplantation experiments, that parasites can egress from AT and repopulate the blood [20]. Thus, it is possible that AT contributes to the relapses also observed in the treatment of African trypanosomiasis, which are typically less than 5–10% after treatment [56,57]. …”
Section: Clinical Relevance and Drug Treatmentmentioning
confidence: 99%
“…First, we provide a large comparative genomic analysis of African trypanosomes of the sub-genus Trypanozoon by analyzing whole genome data from 83 strains from across sub-Saharan Africa, representing a range of human and animal infective types ( S1 Table ), and comprising 21 Tbb , 21 Tbg-1 , 1 Tbg-2 , 35 Tbr and 4 Tev strains (4 Type A and 1 type B). Nineteen of the Tbg-1 strains were isolated from a hospital in the Democratic Republic of the Congo in response to a sleeping sickness outbreak [ 18 ]. Eleven of the newly sequenced strains, and 24 in total, are from Uganda, the only country where both Tbr and Tbg-1 co-occur and where methods of strain discovery can be extremely useful [ 17 ].…”
Section: Introductionmentioning
confidence: 99%